Cardiac CT for intra-cardiac thrombus detection in embolic stroke of undetermined source (ESUS). (September 2022) - Barnea, Rani; Agmon, Inbar Nardi; Shafir, Gideon; Peretz, Shlomi; Mendel, Rom; Naftali, Jonathan; Shiyovich, Arthur; Kornowski, Ran; Auriel, Eitan; Hamdan, Ashraf; ,
Introduction: Embolic stroke of undetermined source (ESUS) is a common medical challenge regarding secondary prevention strategy. Cardiac imaging is the cornerstone of embolic stroke workup, in an effort to diagnose high risk cardio-embolic sources. Cardiac computed tomography angiography (CCTA) is an emerging imaging modality with high diagnostic performance for intra-cardiac thrombus detection. The yield of CCTA implementation in addition to standard care in ESUS workup is unknown. Thus, the aim of this study was to assess the utility of CCTA in detecting intra-cardiac thrombi in the routine ESUS workup. Patients and methods: This is a retrospective observational analysis of ESUS cases managed in vascular neurology unit between 2019 and 2021. Within this ESUS registry, consecutive patients undergoing CCTA were included and carefully analyzed. Results: During the study period 1066 Ischemic stroke (IS) cases were treated and evaluated. 266/1066 (25%) met ESUS criteria and 129/266 (48%) underwent CCTA. Intra-cardiac thrombus was detected by CCTA in 22/129 (17%; 95% CI, 11.5%−23.5%) patients: left ventricular thrombus (LVT) in 13 (10.1%) patients, left atrial appendage (LAA) thrombus in 8 (6.2%) patients, and left atrial (LA) thrombus in 1 (0.8%) patient. Only 5/22 (23%) of these thrombi were suspected, but could not be confirmed, in trans-thoracic echocardiogram (TTE). Among CCTA-undergoing patients, 27/129 (21%; 95% CI, 14%−28%) were found to have an indication (including pulmonary embolism) for commencing anticoagulation (AC) treatment, rather than anti-platelets. In favor of CCTA implementation, 22/266 (8.2%; 95% CI, 4.9%−11.5%) patients within the entire ESUS cohort were diagnosed with intra-cardiac thrombus, otherwise missed. Conclusion: CCTA improves the detection of intra-cardiac thrombi in addition to standard care in ESUS patients. The implementation of CCTA in routine ESUS workup can change secondary prevention strategy in a considerable proportion of patients. Graphical abstract